Modulation of adenosine A2a receptor oligomerisation by receptor activation and PIP2 interactions - Sansom, MSP (Cell Press, 2021)
GPCRs have been shown to form oligomers which generate distinctive signalling outcomes. However, the structural nature of the oligomerization process remains uncertain. We have characterised oligomeric configurations of the adenosine A2a receptor (A2aR) by combining large-scale molecular dynamics simulations with Markov state models. These oligomeric structures may also serve as templates for studying oligomerisation of other Class A GPCRs. Our simulation data revealed that receptor activation results in enhanced oligomerisation, more diverse oligomer populations, and a more connected oligomerisation network. The active state conformation of the A2aR shifts proteinprotein association interfaces to those involving intracellular loop ICL3 and transmembrane helix TM6. Binding of PIP2 to A2aR stabilises protein-protein interactions via PIP2-mediated association interfaces. These results indicate that A2aR oligomerisation is responsive to the local membrane lipid environment. This in turn suggests a modulatory effect on A2aR whereby a given oligomerisation profile favours the dynamic formation of specific supra-molecular signalling complexes.